Ifosfamide-related encephalopathy with severe clinical presentations in children with cancer. (December 2021) - Ataseven, Eda; Göktepe, Şebnem Önen; Kantar, Mehmet
Introduction: Ifosfamide is an alkylating agent, mostly used against variety of solid tumors in pediatric oncology practice. Although hemorrhagic cystitis is known as a common adverse effect, encephalopathy is the another one that should be kept in mind. It may occur in 2–5% of the children, and manifested by different clinical spectrums such as somnolence, lethargy, irritability, excitement, disorientation, confusion, weakness, hallucinations, seizures, movement disorders, and coma. Case report: Herein, we present two patients who developed generalized seizure activity and one who developed coma during ifosfamide infusion. Management and outcome: In the first two patients, ifosfamide infusion was discontinued and intravenous diazepam was given. Their seizure stopped in a few minutes and neurological examination was back to normal, and no focal deficits were observed. In the third patient, ifosfamide infusion was discontinued, methylene blue and thiamine were given. After the tenth dose of methylene blue, she became neurologically normal, without any mental and motor deficit. Nevertheless, later she developed febrile neutropenia, septic shock and she died. Discussion: These cases highlight that pediatric oncologists and hematologists should be aware of possibility of severe neurological toxicity after administration of ifosfamide in adolescent patients. Apart from seizure, clinicians should also be prepared to notice drowsiness during ifosfamide infusions in children. Most of the time cessation of ifosfamide and hydration is enough. However, in severe toxicities there is a risk of irreversible neurological damage, and for these patients methylene blue (MB) and thiamine treatment should be kept in mind.